Regeneración temprana de Chusquea tomentosa (Bambusoideae-Poaceae) en Talamanca, Costa Rica - Grau, Héctor Ricardo (1996)
El documento contiene los siguientes tìtulos:Regeneración temprana de Chusquea tomentosa (Bambusoideae-Poaceae) en Talamanca, Costa RicaMicrobiological quality of some powder spices of common use in Costa RicaFine structure of the capsule of Cryptococcus neoformans(Cryptococcales: Cryptococcaceae)Inhibitory substance residues in unpasteurized and pasteurized milk in a tropical cityCoral colony fragmentation by whitetip reef sharks atCoiba Island National Park, PanamáNest density of Trigona spinipes (Hymenoptera Apidae) in cerrado vegetation of central BrazilHábitos alimentarios de Bufo marinus(Anura Bufonidae)en Costa RicaA case of lapsus calami in Costa Rican scorpion nomenclatureReply to Montoya about the use of the name Chactas bonito